Travel Satisfaction And Revisit Intention In Coastal Tourism Destinations: The Mediating Role Of Destination Satisfaction At Tanjung Bira Beach, Indonesia - Sitti Hasbiah; Ilma Wulansari Hasdiansa (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
Tourism sustainability depends not only on destination attractiveness but also on tourists’ travel experiences and satisfaction. While previous tourism studies have primarily emphasized destination attributes, limited attention has been given to how travel satisfaction influences revisit intention through destination satisfaction, particularly in coastal tourism destinations in Indonesia. Therefore, this study investigates the effect of travel satisfaction on revisit intention through destination satisfaction among tourists visiting Tanjung Bira Beach, Indonesia. A quantitative approach was employed using a survey of 120 tourists, and the data were analyzed using Structural Equation Modeling (SEM) with AMOS 22.0. The results indicate that travel satisfaction positively and significantly affects destination satisfaction (β = 0.712, p < 0.001) and revisit intention (β = 0.284, p = 0.003). Destination satisfaction also positively influences revisit intention (β = 0.566, p < 0.001). Furthermore, destination satisfaction significantly mediates the relationship between travel satisfaction and revisit intention (indirect effect = 0.403; 95% CI [0.268, 0.548]). Unlike previous studies focusing primarily on destination characteristics, this study examines how travel satisfaction contributes to revisit intention through destination satisfaction in a coastal tourism context. Practically, the findings suggest that tourism managers should improve not only destination facilities and attractions but also transportation accessibility, travel comfort, and overall travel experiences to strengthen tourist loyalty and encourage repeat visitation.